2014
DOI: 10.1016/j.ijgo.2014.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of heavy menstrual bleeding and experiences of affected women in a European patient survey

Abstract: Many women affected by HMB do not seek medical help, and few of those who do consult physicians report that they have received appropriate treatment. HMB continues to be underdiagnosed and poorly treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
5
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(202 citation statements)
references
References 20 publications
8
157
5
10
Order By: Relevance
“…In this study, the presence of social stigmas associated with menstruation and beliefs passed down from their mothers influenced them to view menorrhagia as an embarrassing disease. These findings resonated with the previous research findings by Fraser et al () and O'Flynn (), in which menstruation was associated with embarrassment even when discussed with close family and friends.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the presence of social stigmas associated with menstruation and beliefs passed down from their mothers influenced them to view menorrhagia as an embarrassing disease. These findings resonated with the previous research findings by Fraser et al () and O'Flynn (), in which menstruation was associated with embarrassment even when discussed with close family and friends.…”
Section: Discussionsupporting
confidence: 91%
“…Economic analyses show that iron-deficiency anemia can be easily cured with low-cost measures, such as through the provision of dietary education at diagnosis. Severe anemia develops when iron deficiency is not prevented and/or controlled, which impacts a woman’s physical, mental, and social health and becomes a significant public health issue 7,10,11. Any visit a woman makes to the hospital for any type of complaint, especially when blood samples are drawn for diagnostic purposes, is an opportunity to evaluate the patient with respect to anemia and to provide them with need-based treatment, dietary and lifestyle advice, and reproductive health information and precautions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognised and reported that amenorrhoea and oligomenorrhoea are common in elite athletes typically as a result of relative energy deficiency;2 however, little is known about the prevalence of other menstrual abnormalities. Heavy menstrual bleeding (HMB or menorrhagia ) affects a quarter of the general population,3 yet no data exist for athletes or exercising women. It is possible that HMB might impact significantly on women's participation in sport.…”
mentioning
confidence: 99%